Assessment of Smart Technologies Implementation in Challenged People Life in Tomsk; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 26 : Responsible Research and Innovation (RRI 2016) - Makienko M. A. Marina Alekseevna (2017, 2017)
Title screen